Margarita Sánchez Romero (2022). Prehistory of women. Spain: Destino (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2024)
Review of Margarita Sánchez Romero's Book on women in Prehistory.
Keywords: Prehistoric; Gender; Women